Recognizing the concepts of problem-solving strategy and its advantages in teaching speaking - yusrida, Yusrida (State Islamic University of Sultan Syarif Kasim Riau, 2012)
The use of appropriate strategy in teaching speaking is always becoming an expected thing by the teacher because this strategy can help him bring the students toward the success of the teaching. Problem- solving strategy is known as one of the best one in teaching speaking. By knowing and understanding the concepts of problem- solving, the teacher feels helped to develop this strategy into activities supporting the improvement of students’ speaking ability. Selecting the appropriate situations of the problem- solving will motivate the students to speak and find the solution of the problem discussed.